ANALYSIS OF ECONOMIC CONJUNCTURE ON THE COLLECTION AND DISTRIBUTION OF ZAKAT, INFAQ, AND SADAQAH (ZIS) AND PROVINCIAL ECONOMIC GROWTH IN INDONESIA - Rifka Putri Ramadhanty; Muhamad Nafik Hadi Ryandono (Jurnal Ekonomi dan Bisnis Airlangga)
Introduction: This study analyzes the influence of macroeconomic factors—specifically inflation and unemployment—on the collection and distribution of zakat, as well as their impact on provincial economic growth in Indonesia.